Papogi the imaging of Philippine presidents - ABS-CBN News and Current Affairs Division; Philippine Center for Investigative Journalism (Quezon City PCIJ, 2004)
This documentary shows the major archetypes of Philippine politics, the images and characters that aspring politicians have sought to duplicate and resurrect in subsequent elections. "Papogi" posits that the "marketing" of presidents and politicians in this country has been very much like the way movie studios have sold their actors: with flash and dash, and also myth-making and a careful tending of image and storyline.
Disc 1, part 1 (9 min.) -- part 2: Quezon (6 min.) -- part 3: Magsaysay (12 min.) -- part 4: Macapagal and Marcos (12 min.) -- part 5: Marcos (9 min.) -- part 6: Marcos and Aquino (10 min.) -- Disc 2, part 1 Ramos (5 min.) -- part 2: Estrada (9 min.) -- part 3 (10 min.)
This documentary was funded by the Ford Foundation.
VCD.
Philippine Center for Investigative Journalism, producer ; Butch Perez, director ; Joey Reyes, writer, narrator and host.
Keywords: Presidents -- Elections. -- Philippines; Public opinion -- Philippines; Philippines -- Politics and government